Medical Mindfulness Intervention Program: Pathway to Enhancing Mindfulness, Self-Management Efficacy, and Quality of Life of Breast Cancer Patients - Han, Yuanyuan; Agunod, Cyrelle D. (International Journal of Public Health and Medical Research, 2024)
This study evaluates the effectiveness of a mindfulness-based nursing intervention in enhancing mindfulness, self-management efficacy, and quality of life in breast cancer patients. Using a randomized controlled trial design, 80 participants were divided into intervention (n=40) and control (n=40) groups. The intervention group participated in an 8-week mindfulness program, while the control group received standard care. Results demonstrated significant improvements in mindfulness, self-management efficacy, and quality of life in the intervention group. This suggests that mindfulness training could serve as a valuable supportive therapy for promoting psychological well-being in breast cancer patients.